Ingestion of staphylococcus aureus by neutrophils from patients with cystic fibrosis and the effect of surfactant protein-D. (4th April 2011) - Timmis, A; Madsen, J; Clark, H
Abstract : Introduction: Cystic Fibrosis (CF) lung disease is characterised by chronic bacterial infections and intense neutrophil-dominated inflammation. A paradox remains that, despite being hugely abundant in airways, neutrophils fail to eradicate pulmonary infections. Surfactant Protein D (SP-D) acts in first-line immune defence of the lung by binding to pathogens and promoting their phagocytosis. SP-D is decreased in the bronchoalveolar lavage fluid of CF patients. This study aims to answer the following questions: ▶ Is there a difference in the capacity of CF and non-CF neutrophils to ingest bacteria? ▶ Is there a difference in the capacity of CF blood and CF sputum neutrophils to ingest bacteria? ▶ Does SP-D enhance bacterial ingestion by CF neutrophils? Methods: Neutrophils were isolated from blood and sputum taken from CF patients and healthy controls. Neutrophils were incubated with Alexa-488 labelled Staphylococcus aureus and either SP-D, serum or a combination of both. Extracellular S. aureus was removed and the extent of ingestion was determined by flow cytometry. Results: (1) No significant difference was found regarding the capacity for S. aureus ingestion between control blood and CF blood neutrophils. (2) The amount of bacteria ingested by CF sputum neutrophils was found to be significantly lower in comparison to that ingested by CF blood neutrophils. (3) SP-D did not enhance ingestion of bacteria in any of the three groups. In contrast, addition of serum caused improved bacterial ingestion for all three. Conclusions: The study has found greatly reduced function of sputum neutrophils which offers a partial explanation for the poor pulmonary innate immune response in CF, although further work is required to elucidate the reasons behind this poor function of sputum neutrophils. SP-D did not show improvement of neutrophil function in this study, but several potential avenues of research to build upon these findings are identified.